MitoHOPE: Introduction to the Australian Mitochondrial Donation Project - John Carroll (Fertility & Reproduction, 2023)
Mitochondrial Donation provides a means of reducing the risk of transmitting mitochondrial genetic disease. If successful, families who have suffered in many cases across generations, will be freed from the risks of inheriting mitochondrial genetic disease in their future children. In response to mito community advocacy led by the Mito Foundation, Maeve’s Law, was passed in March 2022 to allow the introduction of mitochondrial donation in Australia. The mitochondrial donation procedure involves removing the nuclear DNA from the egg or zygote of from a woman with a mitochondrial DNA (mtDNA) mutation and transferring it to an enucleated egg or zygote from a donor with healthy mtDNA. Although this technique has been used in animal models for many years and has undergone significant preclinical testing in humans, it is use in the clinic remains at an early stage and, to date, only a small number of babies have been born. To introduce mitochondrial donation in Australia, an extensive regulatory and licensing procedure has been established and the MRFF has funded a Mitochondrial Donation Pilot Program, including a clinical trial. The mitoHOPE (Healthy Outcomes Pilot and Evaluation) Program integrates expertise in clinical genetics, oocyte and embryo development, mitochondrial disease, reproductive technologies, ethics, law, and health economics. The program was developed in conjunction with the mito community and this engagement will inform all steps of the implementation. Our partners include Monash IVF, the Mito Foundation and Newcastle University (UK). Progress is now underway to establish our governance arrangements, an oocyte donation program, clinical pathways into the clinical trial and an underpinning research program to ensure the safety and efficacy of mitochondrial donation as it is being introduced into the clinic.